Evaluating institutional capacity for research ethics in Africa: a case study from Botswana - Hyder, Adnan A (BioMed Central, 2013)
BACKGROUND: The increase in the volume of research conducted in Low and Middle Income Countries (LMIC), has brought a renewed international focus on processes for ethical conduct of research. Several programs have been initiated to strengthen the capacity for research ethics in LMIC. However, most such programs focus on individual training or development of ethics review committees. The objective of this paper is to present an approach to institutional capacity assessment in research ethics and application of this approach in the form of a case study from an institution in Africa. METHODS: We adapted the Octagon model originally used by the Swedish International Development Cooperation Agency to assess an organization along eight domains in research ethics: basic values and identity; structure and organization; ability to carry out activities; relevance of activities to stated goals; capacity of staff and management; administrative, financing and accounting systems; its relations with target groups; and the national context. We used a mixed methods approach to collect empirical data at the University of Botswana from March to December 2010. RESULTS: The overall shape of the external evaluation Octagon suggests that strengths of the University of Botswana are in the areas of structure, relevance, production and identity; while the university still needs more work in the areas of systems of finance, target groups, and environment. The Octagons also show the similarities and discrepancies between the 'external' and 'internal' evaluations and provide an opportunity for exploration of these different assessments. For example, the discrepant score for 'identity' between internal and external evaluations allows for an exploration of what constitutes a strong identity for research ethics at the University of Botswana and how it can be strengthened. CONCLUSIONS: There is a general lack of frameworks for evaluating research ethics capacity in LMICs. We presented an approach that stresses evaluation from both internal and external perspectives. This case study highlights the university's rapid progress in developing research ethics capacity and points to some notable areas for improvement. We believe that such an empirically-driven and participatory assessment allows a more holistic measurement and promotion of institutional capacity strengthening for research ethics in LMICs.